Question: How this ODE will be zero-the result in not acceptable why?

this equation will be solve by changing variable but when  i found the function and substitute the ODE is not zero where  is mistake?

restart

with(PDEtools); _local(gamma)

Warning, A new binding for the name `gamma` has been created. The global instance of this name is still accessible using the :- prefix, :-`gamma`.  See ?protect for details.

 

undeclare(prime)

`There is no more prime differentiation variable; all derivatives will be displayed as indexed functions`

(1)

declare(phi(x, t)); declare(psi(x, t)); declare(U(xi))

phi(x, t)*`will now be displayed as`*phi

 

psi(x, t)*`will now be displayed as`*psi

 

U(xi)*`will now be displayed as`*U

(2)

with(PDEtools)

with(LinearAlgebra)

NULL

with(SolveTools)

undeclare(prime)

`There is no more prime differentiation variable; all derivatives will be displayed as indexed functions`

(3)

ode := (diff(diff(U(xi), xi), xi))*lambda^2+(diff(diff(diff(diff(U(xi), xi), xi), xi), xi))*lambda*k^3-6*(diff(diff(U(xi), xi), xi))*k^2*(diff(U(xi), xi))*lambda = 0

(diff(diff(U(xi), xi), xi))*lambda^2+(diff(diff(diff(diff(U(xi), xi), xi), xi), xi))*lambda*k^3-6*(diff(diff(U(xi), xi), xi))*k^2*(diff(U(xi), xi))*lambda = 0

(4)

W := diff(U(xi), xi) = T(xi)

diff(U(xi), xi) = T(xi)

(5)

ode1 := lambda^2*T(xi)+lambda*k^3*(diff(diff(T(xi), xi), xi))-3*k^2*lambda*T(xi)^2 = 0

lambda^2*T(xi)+lambda*k^3*(diff(diff(T(xi), xi), xi))-3*k^2*lambda*T(xi)^2 = 0

(6)

K := T(xi) = A[0]+A[1]*(exp(2*xi)-1)/(exp(2*xi)+1)+A[2]*(exp(2*xi)-1)^2/(exp(2*xi)+1)^2+B[1]*(exp(2*xi)+1)/(exp(2*xi)-1)+B[2]*(exp(2*xi)+1)/(exp(2*xi)-1)

T(xi) = A[0]+A[1]*(exp(2*xi)-1)/(exp(2*xi)+1)+A[2]*(exp(2*xi)-1)^2/(exp(2*xi)+1)^2+B[1]*(exp(2*xi)+1)/(exp(2*xi)-1)+B[2]*(exp(2*xi)+1)/(exp(2*xi)-1)

(7)

case1 := [k = (1/2)*A[2], lambda = -(1/2)*A[2]^3, A[0] = -A[2], A[1] = 0, A[2] = A[2], B[1] = -B[2], B[2] = B[2]]

[k = (1/2)*A[2], lambda = -(1/2)*A[2]^3, A[0] = -A[2], A[1] = 0, A[2] = A[2], B[1] = -B[2], B[2] = B[2]]

(8)

F1 := subs(case1, K)

T(xi) = -A[2]+A[2]*(exp(2*xi)-1)^2/(exp(2*xi)+1)^2

(9)

F2 := subs(case1, ode1)

(1/4)*A[2]^6*T(xi)-(1/16)*A[2]^6*(diff(diff(T(xi), xi), xi))+(3/8)*A[2]^5*T(xi)^2 = 0

(10)

odetest(F1, F2)

0

(11)

subs(F1, W)

diff(U(xi), xi) = -A[2]+A[2]*(exp(2*xi)-1)^2/(exp(2*xi)+1)^2

(12)

E := map(int, diff(U(xi), xi) = -A[2]+A[2]*(exp(2*xi)-1)^2/(exp(2*xi)+1)^2, xi)

U(xi) = A[2]*((1/2)*ln(exp(2*xi))+2/(exp(2*xi)+1))-A[2]*xi

(13)

odetest(E, ode)

32*A[2]*exp(8*xi)*lambda*k^3/(exp(2*xi)+1)^5-352*A[2]*exp(6*xi)*lambda*k^3/(exp(2*xi)+1)^5+192*A[2]^2*exp(6*xi)*lambda*k^2/(exp(2*xi)+1)^5+8*A[2]*exp(8*xi)*lambda^2/(exp(2*xi)+1)^5+352*A[2]*exp(4*xi)*lambda*k^3/(exp(2*xi)+1)^5-192*A[2]^2*exp(4*xi)*lambda*k^2/(exp(2*xi)+1)^5+8*A[2]*exp(6*xi)*lambda^2/(exp(2*xi)+1)^5-32*A[2]*exp(2*xi)*lambda*k^3/(exp(2*xi)+1)^5-8*A[2]*exp(4*xi)*lambda^2/(exp(2*xi)+1)^5-8*A[2]*exp(2*xi)*lambda^2/(exp(2*xi)+1)^5

(14)
 

NULL

Download problem.mw

Please Wait...